Mycelial traits and GRSP in enhancing soil stability on cold region highway slopes: Comparative effects of three shrub species - Yibo Li; Mingxin Zhou; Nan Li; Fei Ye; Li Yin; Hongtao Ma; Xingliang Xu (PLoS ONE, 2025)
In cold regions, the stability of highway slopes is crucial for infrastructure preservation, yet it remains highly vulnerable to soil erosion. This study investigated the role of mycelial traits in reinforcing soil aggregate stability by examining three shrub species—Amorpha fruticosa Linn. (AFL), Lespedeza bicolor Turcz. (LBT), and Swida alba Opiz. (SAO)—across two slope gradients (30° and 60°) in northeastern China. We measured water-stable aggregates, glomalin-related soil protein (GRSP) fractions, and mycelial traits. Results showed that AFL exhibited significantly greater aggregate stability than LBT and SAO, with its stability values 23.1–36.9% higher at the steep slope and 8.7–30.4% higher at the gentle slope. Strong correlations (r > 0.90) between EE-GRSP, mycelial traits, and aggregate stability explained up to 95.1% of the variance on gentle slopes, demonstrating a synergistic trait-based mechanism. However, slope gradient altered this coupling: GRSP efficacy diminished under steep slopes, leaving mycelial traits as the dominant driver of soil stability. These findings reveal a slope-dependent reallocation between physical scaffolding and biochemical adhesion, highlighting AFL and its mycelial traits as critical for slope stabilization in cold regions. The study provides a mechanistic basis for selecting shrub species in slope restoration and offers practical insights into erosion control under global change.